A prospective analysis of the efficiency in the reorganisation process of Italian seaports - Quintano, Claudio (Array, 2020)
The purpose of this paper is to compare the competitiveness of Italian seaports in terms of efficiency scores as a result of significant policy changes adopted in September 2016. An appropriate data set on seaport activities is used that consists of input and output variables obtained by fixing the statistical classification of economic activities (NACE codes) of a sample of 10,763 active firms involved in the new Italian Port Network Authorities (AdSPs). The investigation analyses the major causes of inefficiency and may be viewed as an analysis of the potential of each AdSP, rather than an analysis based on already existing entities. In the authors’ opinion, the results of the data envelopment analysis (DEA) are suitable to support policy decisions designed to improve operational performance of inefficient AdSPs. The empirical analysis reveals several findings that can be extended to different territorial districts.